Sequence of educational error (Journal of the College of Basic Education, 2022)
Educational decisions are the policy of a country in the future consideration of the reality of the country, especially a country like Iraq that lived through societal and economic crises that ate the nature of the realistic thought of a developed green and dry, and therefore we find an urgent need today, as we are on the cusp of the end of the first quarter of the third millennium, to reconsider, and evaluate accurately and honestly the educational decision (The Political) and its impact on the educational reality and its outputs in Iraq.